The use of grammar learning strategies by law students in writing opinion text - Prihatini, Arti; Pangesti, Fida (LITERA, 2023)
Writing is a big problem for law students because of the lack of grammar mastery, limited interactions during the pandemic, and lack of motivation. This study aims to fill the need for investigations about social and affective strategies, part of grammar learning strategies, in writing opinion texts by law students during the pandemic. This study used a mix-method. The respondents were 245 first-year law students at the University of Muhammadiyah Malang. Data collection used inventory and open-ended questions. The results showed that the affective strategy average was 3.30 (medium), while the social strategy was 3.50 (high). The correlation between all social and affective strategies tends to be high, 0.73990. However, the correlation of each strategy in it varies, ranging from very weak to very strong. Even though there are limited interactions, they still use social strategies to overcome the problems of implementing grammar in writing. The dominant social strategy is using corrective feedback on writing by lecturers and other students and learning from people who are more proficient in grammar. On the other hand, the significant affective strategy was trying to relax when having problems understanding grammar and motivating to master grammar. These findings have pedagogical implications for grammar learning strategies in writing to law.Keywords: affective strategies, grammar learning strategies, social strategies, law, writing of opinion text